2015
DOI: 10.1111/dmcn.12769
|View full text |Cite
|
Sign up to set email alerts
|

Teaching reading to children with neurofibromatosis type 1: a clinical trial with random assignment to different approaches

Abstract: AIM Neurofibromatosis type 1 (NF1) is a genetic disorder with a cognitive profile that includes visual–spatial perception deficits and a high incidence of reading disability. There is a paucity of information about how this cognitively complex population responds to mainstream reading interventions. The clinical trial goals were to determine whether children and adolescents with NF1 and reading deficits (NF+RD) benefit from mainstream remedial reading programs and whether responsiveness varies with differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Although further cognitive impairment could be predicted in children with NF1 and concomitant ADHD, some studies have shown no difference in specific skills between NF1 children with ADHD and children with NF1 only. Moreover, Barquero et al ( 11 ) found that scores for ADHD symptoms according to Conners Parent Rating were similar in the four reading groups assessed (NF1 and reading impairment, idiopathic reading deficit, reading deficit reading group, and typical development). In addition, Payne et al ( 22 ) studied SWM and inhibitory control in NF1 children with and without comorbid ADHD.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Although further cognitive impairment could be predicted in children with NF1 and concomitant ADHD, some studies have shown no difference in specific skills between NF1 children with ADHD and children with NF1 only. Moreover, Barquero et al ( 11 ) found that scores for ADHD symptoms according to Conners Parent Rating were similar in the four reading groups assessed (NF1 and reading impairment, idiopathic reading deficit, reading deficit reading group, and typical development). In addition, Payne et al ( 22 ) studied SWM and inhibitory control in NF1 children with and without comorbid ADHD.…”
Section: Resultsmentioning
confidence: 96%
“…Barquero et al ( 11 ) conducted the first evaluation of an intervention for reading deficiencies in 49 children with NF1. Some children received remedial reading instruction from a kinesthetic reading program and others used a program that required greater visuospatial demands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are empirically supported interventions that address either reading fluency (Chard, Vaughn, & Tyler, 2002;Wolf & Katzir-Cohen, 2001) or math fact fluency (Codding, Burns, & Lukito, 2011;Fuchs et al, 2010) in TD individuals, there are as yet very few data on the implementation of these programs for individuals with neurodevelopmental disorders such as SBM. For example, we know of only one small case study where an intervention that is efficacious for addressing weak academic skills in TD individuals (math) was shown to also be beneficial in SBM (Coughlin & Montague, 2011), although Barquero, Sefcik, Cutting, and Rimrodt (2015) did implement a reading intervention for individuals with reading difficulty with and without neurofibromatosis.…”
Section: Summary and Implicationsmentioning
confidence: 99%